19‐2: Invited Paper: Design of Multi‐Resonance Thermally Activated Delayed Fluorescence Materials for Organic Light‐Emitting Diodes. Issue 1 (28th June 2021) - Madayanad Suresh, Subeesh; Duda, Eimantas; Kahle, Frank-Julian; Hall, David; Bagnich, Sergey; Bässler, Heinz; Beljonne, David; Olivier, Yoann; Köhler, Anna; Zysman-Colman, Eli
Abstract : The development of near UV‐emitting materials will be presented. A novel ladder‐like multiresonant thermally activated delayed fluorescence (TADF) compound was studied in the solid state. The compound shows narrow near UV‐emission centered at 395 nm of optical excitation and at 410 nm in an OLED; however, the efficiency remains low. Photophysical studies reveal the presence of aggregate or excimer‐like species that seem to provide an additional loss channel.